Analysis of aluminum plates under heating in electrical and natural gas furnaces - Magalhães Sobrinho, Pedro [UNESP]; Carvalho Jr., João A. [UNESP]; Luz Silveira, José [UNESP]; Magalhães Filho, Paulo [UNESP] (Elsevier B.V., 2000)
This paper analyzes the thermal storage characteristics of aluminum plates in furnaces during their heating for lamination under two sources of heat: an electrical resistance bank and a combustion process carried out with natural gas. The set of equations to model the furnace under operation with electrical energy, for air as the fluid, is presented. This supports the theoretical analysis for the system under operation with natural gas combustion products. A numerical procedure, using the software ANSYS, is applied to determine the convection heat transfer coefficients for heating by the air flow. Temperatures measured in a plate inside a real furnace are used as parameters to determine these coefficients. Then convection and radiation heat transfer coefficients are determined for the natural gas combustion products. Results are compared, indicating a possible gain of 5.5 h in relation to a 19.5 h period of conventional electrical heating per plate.
Keywords: Aluminum; Computer simulation; Electric furnaces; Gas furnaces; Heat transfer coefficients; Mathematical models; Plates (structural components); Thermodynamic stability; Software package ANSYS; Heat storage